Sucos funcionais: percepções, compreensão e comportamento do consumidor - Costa, Marcelo Martins da (2019)
With increasing awareness and concern about health, understanding of the importance of food for maintaining well-being, reducing disease risk and extending life expectancy, consumers are seeking to increase knowledge about the properties of the foods in order to make better choices for healthy eating. In this scenario, functional foods have been growing, with new products being developed and launched every year. However, this is still a new food group in Brazil, and consumers have neither a clear understanding nor a clear perception of their characteristics. This dissertation takes a qualitative approach, using a collection method through focus groups with consumers of ready-to-drink juices and uses a semi-structured script developed based on the Health Belief Model (HBM) and Theory of Planned Behavior (TPB) to identify the beliefs and motivation of these consumers. As a theoretical contribution it is presented an integrated model of these theories and, as an industry contribution, a mapping of the barriers to be overcome for the launching of a functional food. The objective of this dissertation is to identify the understanding and perception of São Paulo consumers in relation to functional foods, with the following specific objectives: (i) to identify how consumers interpret and position different product variations in the category of ready-to-drink juices; (ii) identify how consumers interpret the generic definition of functional foods, what products available on the market in the category of ready-to-drink juices are identified with these characteristics and how they are called; (iii) identify the consumer's understanding of a specific functional product: a juice with essential nutrients to complement the diet.